MANAJEMEN RANTAI PASOKAN HIJAU DAN KINERJA BISNIS: PERAN KINERJA OPERASIONAL PADA SEKTOR INDUSTRI PRODUK HALAL - Muhammad Ali Fikri; Poppy Laksita Rini (Jurnal Ilmiah Ekonomi Islam, 2023)
The implementation of green supply chain management can improve operational performance as well as business performance. This study aims to analyze the effect of green supply chain management on business performance through operational performance. A survey is conducted on micro, small, and medium enterprises in the halal product industry sector. The results of this study indicate several findings which are: (1) green supply chain management has a positive effect on business performance, (2) green supply chain management has a positive effect on operational performance, (3) operational performance has a positive effect on business performance, and (4) operational performance mediates the positive effect of green supply chain management on business performance.